Sustainability Development in Hospitality: The Effect of Perceived Value on Customers’ Green Restaurant Behavioral Intention - Yi-Man Teng (Sustainability, 2019)
Recently, sustainability management has developed in the hospitality industry. Green restaurants have been progressively joining the hospitality industry. Consumer patronage determines the sustainable development of the green restaurant. This paper aims to explore the structural relationships among perceived values (hedonic and utilitarian values), consumer preference and behavior intentions of the green restaurant. A total of 278 valid questionnaires were collected, and the partial least squares (PLS) method was utilized to measure and test the research hypotheses. The study presents empirical evidence showing that hedonic and utilitarian values have significantly and positively affected consumer preferences for green restaurants and that utilitarian value and customer preferences have significantly and positively influenced behavior intentions of green restaurant. Furthermore, the results also demonstrate that consumer preferences partially mediate the relationships between utilitarian value and behavior intentions of the green restaurant. Finally, theoretical and practical implications are discussed and suggestions for future research are provided.